Analysis of the Australian Government’s Security Strategy in Countering the Potential Threat of Terrorism Groups Through Cyber Terrorism Instruments - Cantika, Suci; Umniyah, Annisa (Insignia: Journal of International Relations, 2023)
This paper discusses the strategies adopted by Australia in dealing with and overcoming the violent acts of Cyber Terrorism. Since the terrorist attack on September 11, 2001 in the United States, countries in the world have assumed the existence of terrorist groups as a global threat. Globalization has enabled the terrorist groups to transform conventional media in the cyber world into the infamous cyber terrorism which they use as a propaganda instrument for recruitment, providing logistics, training, forming paramilitaries, planning, carrying out attacks, hiding, and funding. This paper discussed the concept Australian national security which has developed beyond military. The concept of security according to the non-traditional approach is emphasized on the security interests of non-state actors (non-state actors). The present research used descriptive qualitative research, employing literature review or library research for data collection. The results found that the Australian government remains vigilant against cyberterrorism through law enforcement and international cooperation. The Australian government has stipulated the Criminal Code Act 1995 part 5.3 to fight against the acts of terrorism. In addition, to increase domestic skills in cyberspace, The Australian government also establish Australia's Cyber Security, through which the Australian Cyber Security Centre (ACSC) founded Joint Cyber Security Centres (JCSCs), AustCyber, the Australian Cyber Security Growth Network, and the Cyber Security Cooperative Research Centre. and. Australia is also committed to supporting and maintaining international mechanisms that promote stability and to working with partners on a voluntary basis to prevent and respond to threats, including cyber terrorism. Keywords: Australia, cyber terrorism, national security